Openness in scholarship: A return to core values? - Neylon, Cameron (2017)
© 2017 The authors and IOS Press. The debate over the meaning, and value, of open movements has intensified. The fear of co-option of various efforts from Open Access to Open Data is driving a reassessment and re-definition of what is intended by "open". In this article I apply group level models from cultural studies and economics to argue that the tension between exclusionary group formation and identity and aspirations towards inclusion and openness are a natural part of knowledge-making. Situating the traditional Western Scientific Knowledge System as a culture-made group, I argue that the institutional forms that support the group act as economic underwriters for the process by which groups creating exclusive knowledge invest in the process of making it more accessible, less exclusive, and more public-good-like, in exchange for receiving excludable goods that sustain the group. A necessary consequence of this is that our institutions will be conservative in their assessment of what knowledge-goods are worth of consideration and who is allowed within those institutional systems. Nonetheless the inclusion of new perspectives and increasing diversity underpins the production of general knowledge. I suggest that instead of positioning openness as new, and in opposition to traditional closed systems, it may be more productive to adopt a narrative in which efforts to increase inclusion are seen as a very old, core value of the academy, albeit one that is a constant work in progress.